1976
DOI: 10.1289/ehp.7618167
|View full text |Cite
|
Sign up to set email alerts
|

Model ecosystem evaluation of the environmental impacts of the veterinary drugs phenothiazine, sulfamethazine, clopidol, and diethylstilbestrol.

Abstract: Four veterinary drugs of dissimilar chemical structure were evaluated for environmental stability and penchant for bioaccumulation. The techniques used were I1) a model aquatic ecosystem (3 days) and (2) a model feedlpt ecosystem 133 days I in which the drugs were introduced via the excreta of chicks or mice. The model feedlot ecosystem was supported by metabolism cage studies to determine the'amount and the form of the drug excreted by the chicks or mice. Considerable quantities of all,the drugs were excreted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The unextractable radioactivity represented 88.6% of the total radioactivity in alga, 19.9% in snail, 47.9o in mosquito, and 61.9% in fish. The overall environmental behavior of dibenzothiophene was very similar to that observed in comparable studies with '4C-phenothiazine (23 (25) and these lead to ready conjugation and excretion. Benzo[a]pyrene is also highly photodegradable.…”
Section: Model Ecosystem Evaluationsupporting
confidence: 72%
“…The unextractable radioactivity represented 88.6% of the total radioactivity in alga, 19.9% in snail, 47.9o in mosquito, and 61.9% in fish. The overall environmental behavior of dibenzothiophene was very similar to that observed in comparable studies with '4C-phenothiazine (23 (25) and these lead to ready conjugation and excretion. Benzo[a]pyrene is also highly photodegradable.…”
Section: Model Ecosystem Evaluationsupporting
confidence: 72%
“…Previous soil fate studies have indicated that SMZ is not strongly sorbed to soils and is likely to be highly mobile in the aqueous portion of runoff, thus being likely to reach surface water bodies, e.g. small ponds (5,(10)(11)(12). Though its fate has been extensively examined in soil, SMZ fate in surface water, and sediment in particular, has not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…The prototypical estrogen compound diethylstilbestrol (DES) has been well studied, in that four studies have been conducted on six different species. Coats et al ( 1976 ) investigated the acute toxicity of DES on algae, invertebrates, and fi sh, identifying invertebrates ( Culex pipiens and D. magna ) as the most sensitive group (48-h LC 50 = 4 mg/L). Baldwin et al ( 1995 ) and Zou and Fingerman ( 1997 ) reported D. magna to be even more sensitive than previously reported to DES exposure, based on 48-h LC 50 values ranging from 1.1 to 1.2 mg/L; however, EE2 is signifi cantly more acutely toxic than DES to algae (EC 50 = 0.84 mg/L) and fi sh (96-h EC 50 = 1.6 mg/L) (Kopf 1995 ;Schweinfurth et al 1996 ) .…”
Section: Estrogens and Antiestrogensmentioning
confidence: 99%